Gestión por procesos en la logística en una empresa PYME del sector construcción - LLaque Fernández, Grant Ilich (2022)
The objective of this research is to determine to what extent Process Management influences the Logistics of the construction company Dayro Contractistas S.R.L, 2019. It is applied with a pre-experimental design and used the methodology for the implementation of Management by Processes in public administration entities. The current situation was analyzed by applying surveys and observation files to a sample of 04 collaborators from the Logistics area, from 02 processes from the same area in Moche and Chao. Subsequently, Process Management was implemented through the documentation of the process map, process inventory, files, diagrams and procedures, design of formats, as well as the establishment of policies and indicators. The new processes were communicated through a training entitled “Building an Effective Logistics”. It concludes that the implementation of Management by Processes significantly influences Logistics, reaching a decrease of 79.61% in the old age of the inventory (p = - 14.58 <0.05) and an improvement on the delay in the search for materials in 69.25% (p = - 10.53 <0.05). Finally, the implementation is viable generating a NPV of S /. 106 792.90 soles, and an IRR 125.83%.